Turnover intention and influential factors among primary healthcare workers in Guangdong province, China: a cross-sectional study - Xia Li; JianLi Wang; Ningning Wang; Lian He; Caiwen Li; Yinmei Xie; Anfei Luo; Zhiwei Lu (BMJ Open)
Objectives Primary health workers are crucial to the healthcare system, yet China experiences a notable shortage driven by high turnover rates. This study aimed to investigate the prevalence and determinants of turnover intention among primary health workers.Design Cross-sectional study.Setting Primary healthcare facilities across 21 cities in Guangdong province, China.Participants Online questionnaires (SurveyStar, Changsha Ranxing Science and Technology) were administered to 16 573 primary health workers in September and October 2022.Primary and secondary outcome measures Variables measured included demographics, work-related factors, job satisfaction, emotional exhaustion and turnover intention. Comparisons of turnover intention were made across different categorical groups, and hierarchical regression analysis was used to pinpoint influencing factors.Results The average turnover intention score among participants was 10.49±2.93. Notable positive correlations included those with male gender, single marital status, leadership positions and roles as public health physicians. Emotional exhaustion correlated positively (β=0.108), while job satisfaction showed a significant negative correlation (β=−0.154). Other negative influential factors were observed with tenure lengths of 6–10 years, 11–15 years and ≥16 years, as well as with senior professional titles, lower salary levels and perceptions of fair compensation.Conclusions Turnover intention is notably prevalent among primary healthcare workers, with emotional exhaustion and job satisfaction identified as primary determinants. Salary, payment justice in compensation and tenure also significantly influence turnover intention. Based on the above analysis, a series of intervention measures can be expectedly unveiled to reduce the turnover intention of primary health workers and maintained the steady development of basic medical resources.